Charitable Foundations in the Principality of Liechtenstein – Tradition and Recent Developments - Schurr, Francesco A (Victoria University of Wellington Law Review, 2011)
The purpose of this paper is to examine the evolution of the foundation (Stiftung) in the Principality of Liechtenstein. The article therefore deals with recent changes in the statutory legislation governing them as well as with current developments in case law. The paper will also address the different approaches taken towards foundations by the civil law and common law traditions within Europe. In fact, the jurisdiction of Liechtenstein embraces elements of both the civil and the common law traditions.